Artillery and rigging artefacts from the Megadim wreck-site, Israel. (August 2017) - Ashkenazi, D.; Cvikel, D.; Langgut, D.; Rosen, B.; Galili, E.
Abstract: Various artillery and rigging artefacts were retrieved from the Megadim wreck-site, Israel. The present research is aimed at determining the composition, microstructure and manufacturing processes of the objects, as well as their dating. Therefore, a multidisciplinary testing approach was applied, based on typology, metallurgical criteria, archaeobotanical analysis and 14 C radiocarbon dating. Based on their typology, the three cannons found off Megadim were of Venetian origin. Metallurgical analysis of the three cannons revealed they were made of cast bronze, with tin (Sn) composition of 3.2–6.5 wt%; and were most likely manufactured at the same European foundry. The chain links of the iron-bound deadeye were made of wrought-iron, manufactured by the bloomery process; and the forge-welding zone of the largest chain was located. Epi-illuminated and SEM analyses suggest that the deadeyes were made of Rhus coriaria, and the wads were made of Cupressus sempervirens and Pinus pinea . The largest breech chamber was made of cast leaded-bronze, probably manufactured of recycled alloys due to the low amount of tin. The other two chambers were made of wrought-iron, and based on their similar composition, were probably manufactured at the same workshop. Examination of the material extracted from the chambers suggests it was black powder. The bronze cannons were typologically dated to between the late 16th and the early 17th centuries. Based on the metallurgical criteria and the 14 C analysis, it is suggested that all the objects were most likely manufactured before the middle of the 17th century. This research enhances our knowledge of the Megadim wreck-site, and provides better understanding of the manufacturing technologies of marine artillery and rigging elements in Europe between the late 16th and early 17th centuries. Highlights: Various artillery and rigging items from the Megadim wreck-site were examined. The artefacts were made of bronze and wrought-iron. The artefacts were manufactured before the middle of the 17th century. The ship may have originated in a south European, Mediterranean country.